High-temperature metamorphism in the western Namaqua-Natal Metamorphic Province (South Africa): implications for low-pressure granulite terranes - Schorn, Simon (Department of Geological Sciences, 2019)
The interpretation of pressure (P)-temperature (T)-time (t) data is key to reconstruct the geologic evolution of ancient exhumed orogens. Of these, temperature is regarded as proxy for the heat energy available during orogenic metamorphism. Heat - the ultimate driving force of metamorphism - is consumed by a number of processes occurring during orogeny. Metamorphic rocks evolve through chemical reactions that consume energy in order to advance. As long as strongly energy-intensive processes advance in the crust, the temperature that is effectively attained is controlled by the interplay between the rate of heat energy supplied to the site of reaction and the rate of heat consumed by the process(es). Melting reactions in particular are strongly endothermic and consume a substantial proportion of the orogenic heat budget. Fertile metapelites are volumetrically minor but petrologically significant, as P-T-t-deformation constraints and burial-exhumation paths are preferentially derived from this lithology, whereas refractory granites sensu lato compose the bulk of orogenic crust. Metapelites are affected by a number of heat-consuming reactions that cause a near-isothermal state as long as they advance, however granites intersect few endothermic melt-producing reactions during orogenic metamorphism. Granitoids therefore may effectively reach a higher temperature compared to metapelites exposed to the same heat input. Temperature determined from metapelites may therefore not represent the true thermal maximum experienced by a portion of metamorphic crust - especially in granulite terranes where partial melting is widespread. Because temperature is an effect rather than the cause of heat energy transferred into the crust, it may not represent the most geodynamically relevant parameter to describe metamorphism.